2018
DOI: 10.1111/jog.13823
|View full text |Cite
|
Sign up to set email alerts
|

Six‐week pretreatment with growth hormone improves clinical outcomes of poor ovarian responders undergoing in vitro fertilization treatment: A self‐controlled clinical study

Abstract: Aim:The purpose was to explore whether the 6 weeks of growth hormone (GH) pretreatment could increase the live birth rate of poor ovarian responders (POR). Methods: This self-controlled, retrospective study was performed among 380 POR who had GH adjuvant (GH+) at a university-affiliated hospital in Guangzhou, China, from October 2010 to April 2016. Growth hormone was injected daily beginning with the previous menstruation and maintained until ovum pickup, for approximately 6 weeks. Clinical variables between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
(19 reference statements)
3
18
1
1
Order By: Relevance
“…Another study analyzed the effects of 6-week pretreatment with GH in POR which were submitted to an in vitro fertilization treatment. This study, carried out in 380 POR, showed that the administration of the hormone significantly improved the rate of utilization of oocytes and embryo quality increasing the live birth rates, even in older patients who had previously experienced unsuccessful results from classical techniques (85). Moreover, another recent study demonstrated that co-treatment with GH in patients with normal ovarian response significantly increased pregnancy rate (86).…”
Section: Ovarian Functioningmentioning
confidence: 84%
“…Another study analyzed the effects of 6-week pretreatment with GH in POR which were submitted to an in vitro fertilization treatment. This study, carried out in 380 POR, showed that the administration of the hormone significantly improved the rate of utilization of oocytes and embryo quality increasing the live birth rates, even in older patients who had previously experienced unsuccessful results from classical techniques (85). Moreover, another recent study demonstrated that co-treatment with GH in patients with normal ovarian response significantly increased pregnancy rate (86).…”
Section: Ovarian Functioningmentioning
confidence: 84%
“…As stated before, GH adjuvant therapy was clinically widely used in poor ovarian responders (7, 8, 10, 11, 14, 16, 19, 6063, 67–76), poor quality of embryos (16, 17, 67, 70, 74, 77), improper endometrial reaction (5, 12, 56, 78, 79) and repeated implantation failure (1, 63, 8082). When it is used in patients with repeat implantation failure which is defined as failure of pregnancy despite implantation of a high-quality embryo at least three times or of over 10 embryos on repeat implantation failure (1, 63, 8082), the mechanism of this action is, as stated before, related to GH stimulating proliferation and differentiation of granulosa cells, increasing production of estradiol in both early and late follicular development for animal and human ovaries, enhancing effect of FSH on the development of ovarian follicles and improving endometrial thickness (82, 98100).…”
Section: Subjects and Benefits Of Gh Treatmentmentioning
confidence: 99%
“…However, some randomized controlled trials discouraged the use of GH in IVF because no definitive benefits have been demonstrated in increasing the live birth rate for poor responders (18, 19), but careful evaluation of these trials showed severe drawbacks as stated before. Up to now, GH has been widely applied in the reproduction area but primarily for poor ovarian responders (7, 8, 10, 11, 14, 16, 19, 6063, 67–76), poor quality of embryos (16, 17, 67, 70, 74, 77), improper endometrial reaction (5, 12, 56, 78, 79) and repeated failure of embryo transfer (1, 63, 8082).…”
Section: Application Of Gh In Ivfmentioning
confidence: 99%
“…A number of studies have suggested that GH adjuvant therapy increases the number of retrieved oocytes, mature oocytes, and good quality embryos in POR cohorts (18)(19)(20)(21)(22)(23). Moreover, a systematic review, including randomized controlled trials and single center retrospective studies, suggested that the addition of GH in ovarian stimulation increased the probability of clinical pregnancies and live births in PORs (24)(25)(26). However, a recent updated meta-analysis, including the largest multicentered randomized controlled trial (RCT) conducted by the LIGHT investigators failed to find a significant difference in the live birth rate (LBR) after GH adjuvant therapy in PORs (27).…”
Section: Introductionmentioning
confidence: 99%